Perioperative Care In Maxillofacial Surgery- An Updated Review For Healthcare Professionals (The Review of Diabetic Studies, 2024)
Background: Facial lacerations are common injuries that pose significant functional and aesthetic challenges if inadequately managed. Their proximity to critical neurovascular and glandular structures necessitates meticulous perioperative care to minimize complications and long‑term morbidity.Aim: This review aims to provide an updated, anatomy‑based overview of perioperative assessment, repair techniques, and multidisciplinary considerations in facial laceration management.Methods: A narrative review of facial anatomy, indications, contraindications, equipment, techniques, and complications relevant to facial laceration repair was conducted, integrating current clinical standards and operative principles.Results: Optimal outcomes depend on detailed anatomical knowledge, appropriate wound preparation, layered closure guided by relaxed skin tension lines, and early identification of injuries involving the facial nerve, parotid duct, eyelid margin, and lacrimal system. Adjunctive measures, including proper anesthesia, suture selection, and postoperative scar management, significantly reduce infection, dehiscence, and poor cosmetic outcomes.Conclusion: Structured perioperative planning and anatomy‑based repair enhance functional recovery and aesthetic results in facial laceration management.